Three-year dynamics and unsolved problems of lipid-lowering therapy - V. A. Sergeeva (Столичная издательская компания, 2015)
Aim. To study the lipid-lowering therapy, the adequacy of its control, as well as the awareness of patients at a high cardiovascular risk of atherosclerosis problems and the dynamics of these parameters in 3 years. Material and methods. Patients with dyslipidemia (113 patients in 2011 and 100 patients in 2014) who were treated in the cardiology clinic were examined. Patient survey on the lipid-lowering therapy and its monitoring was conducted. Medical records of patients were studied also.  Results. The number of patients informed on atherosclerosis aspects increased from 52% to 59% (p>0.05) in 3 years. Laboratory control of lipid metabolism remained inadequate. Insufficient lifestyle modification changes (diet, smoking, physical inactivity) were present. Lipid-lowering drugs were regularly taken by 26% of the patients in 2011 and 29% in 2014 (p>0.05) and a control of lipid metabolism was absent in 12% and 14% of the patients, respectively (p>0.05). Only 27% of the patients gave the importance of lipid-lowering therapy 10 points on a 10-point scale.  Conclusion. Dynamics of patients awareness on atherosclerosis and measures taken to correct and control lipid metabolism disorders were insignificant within 3 years. High costs of medication and the underestimation of treatment importance by the patient play an important role in poor adherence.